Analysis Of Peer Instruction Flipped Type Of Flipped Classroom Learning Towards Concept Comprehension, Collaboration And Communication Skills - Nabila Fatimah; Aang Suhendar; Septian Karyana; Reza Setiawan (Southeast Asian Journal on Open and Distance Learning, 2023)
This study aims to analyse how peer instruction flipped type of flipped classroom learning can improve students’ concept comprehension and facilitate collaboration and communication skills. The design of this study is quasi-experiment. The sample of this study consists of 45 students in XI MIIA 7 and XI MIIA 8 of SMA Alfa Centauri Bandung. The result showed that the average score of conceptual comprehension of students who learnt through peer instruction flipped of flipped classroom model were higher than the students who learnt through conventional model. Furthermore, flipped classroom type peer instruction flipped type learning gave an effect to collaboration and communication skills.